Cuentas por cobrar de los tributos del Gobierno Autónomo Descentralizado Municipal del Cantón Urdaneta en el periodo 2023. - Padilla Rodríguez, Gloria Judith (2024)
This study addresses a growing issue within the Decentralized Autonomous Government (GAD) of the Urdaneta Canton concerning accounts receivable from taxes. This issue is primarily caused by taxpayer non-compliance, which leads to a reduction in revenue from own activities, resulting in limited financial resources for the institution. The main objective of this research is to analyze the accounts receivable from taxes of the Urdaneta Canton municipal GAD during the year 2023 through the review of the provided accounting information. A mixed methodology was employed with both qualitative and quantitative approaches, combining techniques such as internal control questionnaires, interviews, review of accounting documents, and financial analysis. The study identified an internal control system that requires attention, poor collection management, and a lack of enforcement of collection policies. Financial analysis revealed significant reliance on receivables from potable water, as well as urban and rural properties. The examination of arrears using financial indices showed high levels in areas such as potable water service, construction and expansion projects, and both urban and rural properties, which affects the GAD's financial capacity to execute essential works, services, and projects for community development.